Earthquake in Nepal: A Miserable Environmental Hazard Visited by Nature - Dube, Shiva Kant (Academic Voices: A Multidisciplinary Journal, 2016)
Indian and Tibetan tectonic plates and therefore lies in a seismically active region. Historical data evidence the occurrence of destructive great earthquakes in the past. Earthquakes are caused mainly due to disequilibrium in any part of the crust of the earth. If we look at the world distribution of earthquake, it appears that the earthquake belts are closely associated with the weaker zones of the seismotectonics of the region. It is an instrument for seismic surveillance allowing a fast post-earthquake rescue operation. This paper incorporates a case of earthquake occurred in April, 2015 as one of the environmental hazards visited by nature which proved disastrous causing massive loss of lives and properties to the vulnerable regions. It can be taken as a lesson to mitigate massive loss of lives and properties selecting isostatically proper land structure and constructing safe settlements for habitat in Nepalese context. Academic Voices Vol.5 2015: 56-66